Implementation of Excellent Learning at Elderly Pesantren of Nurul Iman in Karanganyar Regency - Dinar Bela Ayu Naj'ma; Syamsul Bakri (Universitas Muhammadiyah Enrekang, 2022)
This study purposes to (1) determine the implementation of al-Qur'an learning for the Elderly Pesantren Nurul Iman of Karanganyar, (2) describe the implementation of worship fiqih learning for the elderly, and (3) explain the process of character education for the Elderly Pesantren Nurul Iman of Karanganyar. This research was conducted in August 2020 – January 2021. The subjects in this study were all asatidz (teachers) and elderly students of Pesantren Nurul Iman in Karanganyar Regency. Meanwhile, the selected research informants were caregivers, asatidz, students, local government and pesantren education experts. This research applied qualitative methods and case studies. The results reveal that: (1) The implementation of learning the Qur’an for the elderly at Pesantren Nurul Iman Karanganyar is carried out using the Iqro method and the tsaqifa method. Class grouping is based on the individual abilities of elderly students and does not use the average model as the class system in general. This shows that learning the Qur'an for the elderly needs to have attention in the abilities of each elderly student, so that the superior learning method is very relevant to use. (2) The implementation of worship fiqh learning for the elderly at Pesantren Nurul Iman Karanganyar is carried out with the bandongan model. To evaluate the success of learning fiqh of worship, a practicum method is used, namely the practice of fiqh of worship, especially the practice of pasolatan fiqh. With this mentoring model, the process of learning fiqh worship becomes effective, not only in fiqh knowledge but also in worship practices. (3) The process of character education for the elderly at the Elderly Pesantren of Nurul Iman Karanganyar is carried out through integrating character education in rituals and dzikr, sports and arts, in addition to character building through lectures delivered in each study activity. This shows that character education can be effective if it is carried out with affective activities not just cognitive.